Fentanyl: A Whole New World?. Issue 2 (June 2018) - Rothberg, Rachel L.; Stith, Kate
This article seeks to document the latest danger in the opioid crisis: fentanyl and related synthetic opioids. Fifty times more potent than pure heroin, cheaper to manufacture in laboratories worldwide, and easily distributed by mail and couriers, fentanyl is flooding the illicit opioid markets throughout the country.